Stent implantation into ductus arteriosus: a new alternative of palliative treatment of duct-dependent pulmonary circulation - Mulyadi M Djer; Bambang Madiyono; Sudigdo Sastroasmoro; Sukman T Putra; Ismet N Oesman; Najib Advani; Mazeni Alwi (Paediatrica Indonesiana, 2004)
Background The technical aspects of ductal stenting have beenreported, but little is known about the fate of the duct after stentimplantation.Objectives To determine the effects of PDA stenting on the degreeof cyanosis, blood oxygen saturation, long-term patency of PDA,and the growth of pulmonary artery and its branches, in patientswith duct-dependent pulmonary circulation.Methods This was a case series study conducted at the Depart-ment of Pediatric Cardiology, Institut Jantung Negara (National HeartInstitute), Kuala Lumpur, Malaysia from November 1996 to Septem-ber 2001 on patients with duct-dependent pulmonary circulation whounderwent stent implantation. All patients were followed-up until oc-clusion or block occurred or until the end of follow-up time. The evalu-ation consisted of clinical manifestations, electrocardiography, chestx-ray, echocardiography, and cardiac catheterization.Results Stent was successfully implanted in 60 patients (84%),failed in 7 patients (10%) and contra indicated in 4 patients (6%).There was significant improvement on the degree of cyanosis afterstent implantation (p<0.0001). The blood oxygen saturation signifi-cantly increased from 74% (ranged 42-93; SD 12) before proce-dure, to 90% (ranged 62-100; SD 8) afterward (p<0.0001). The meanduration of follow-up time was 14.2 months (ranged 2.5-50.8; SD13) and the minimal patency of PDA was 11.2 months (ranged 1.1-47.7; SD 10.7) after implantation. At the end of follow-up, the stentswere widely patent in 33 patients (55%), stenotic in 15 patients (25%)and spontaneously occluded in 12 patients (20%). There was in-creased growth of pulmonary artery as measured by McGoon ratiofrom 1.23 (ranged 0.4-2.3; SD 0.4) to 1.81 (ranged 0.7-0.9; SD 0.57),and no distortion of pulmonary artery and its branches found.Conclusion Stent implantation into ductus arteriosus decreasedthe degree of cyanosis, increased blood oxygen saturation, main-tained long-term patency of ductus arteriosus, and promoted theincreased growth of pulmonary artery without distortion of pulmo-nary artery and its branches